PERANCANGAN DAN IMPLEMENTASI APLIKASI PENCARIAN RUTE TERPENDEK DATA-DATA SEKOLAH DI KOTA PADANG MENGGUNAKAN ALGORITMA DZIKRA - defni defni (Jurnal Momentum ISSN 1693-752X)
AbstrakThe use of android-based mobile devices can also be in the world benefit from education in Padang city help people in knowing about the data of an existing school inPadang city including directions to know the path to the location of the school it can be made possible by utilizing GPS technology. This article aims to create an application that can find the shortest route from the existing schools in Padang city by using the Dzikra algorithm and is designed for the mobile-based devices namely operating system android and also utilizes GPS technology to pinpoint the location of the school. Key words  :Dzikra algorithm, GPS, Android